An Experimental Comparison of a Problem-Based Learning and a POE-Assisted Project-Based Learning Model of Teaching Scientific Literacy - Ayi Jaja Jamaludin; Syakti Perdana Sriyansyah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Although many previous studies are published to be some evidence of the effectiveness of inductive learning models, an experimental comparison of two inductive learning models of teaching scientific literacy remains unavailable. The purpose of this study, therefore, was to investigate 46 secondary students' scientific literacy through a comparison of problem-based learning and project-based learning that is assisted by using a predict-observe-explain strategy on thematic learning. A quasi-experimental method with alternative treatment (pretest and posttest) with nonequivalent groups design was used to assign students into the experimental and the comparison groups, respectively 25 students who had the POE-assisted project-based learning and 21 students who had the problem-based learning. The normalized change and an analysis of covariance with students' pretest scores as covariates were adopted for data analysis. The results revealed that the average normalized change score of both groups was 69±7 and 39±8, respectively high category for the experimental group and medium category for the comparison group. There were significant differences between both groups' improvement (F=8.356; p<0,006; and Cohens' ES d = 0,83). Thus, the implementation of POE-assisted project-based learning could further improve secondary students' scientific literacy than problem-based learning on thematic learning.Keywords: inductive model, POE strategy, scientific literacy